SOME PROBLEMS OF MATHEMATICAL SIMULATION ON DESCRIBING DEVELOPMENT OF MAGMATIC AND ORE-MAGMATIC SYSTEMS - Dorovskii V.N.; Perepechko Yu.V.; Sharapov V.N. (My University, 1998)
A physically substantiated and mathematically correct dynamic theory of development of magmatic and ore-magmatic systems may be constructed from the general physical principles of the nonequilibrium thermodynamics of condensed media: Galileo's invariance of governing equations, the first law of thermodynamics, fulfillment of conservation laws, and convexity of medium energy as a function of its variables. It is shown that equations of motion may be obtained on the basis of these principles with the method of conservation laws and the variatioal approach. The principle of elaborating such theories is exemplified by constructing models for the dynamics of endogenic processes.